Pentingnya Penerapan Akuntansi Pesantren Study Pada Pondok Pesantren Madrasah Tarbiyah Islamiyah Tanjung Barulak - Sri Adella Fitri; Rumondang Lubis; Soltika Citra; Sri Rahmadani; Wira Julita; Yohana Silvin (JURNAL EKOMAKS Jurnal Ilmu Ekonomi Manajemen dan Akuntansi, 2024)
Abstract— Pesantren is a religious institution that needs to have supporting infrastructure within the institution itself in order for pesantren to live a normal life. Precise in meaning is not just common in the field of infrastructure; it also requires consideration of administration and the organization of the kelembangan. The MTI Islamic Boarding School Education Foundation is a non-profit organization for religious education that was founded in the year 1930 and is located beneath the Ministry of Religion. Generally speaking, the NGOs as well as a few students and students as well as government assistance made up the sum of the funding for Islamic boarding schools in question. The purpose of this study is to understand how assurance is carried out regarding the amount of money that is deposited and withdrawn from the MTI pesantren. The study was conducted using a qualitative methodology and involved gathering data over the course of two months, from April to May, and analyzing and analyzing one single study participant, treasurer. From the study's findings, it is possible to infer that